2006
DOI: 10.1038/sj.onc.1209582
|View full text |Cite
|
Sign up to set email alerts
|

Calpain 2 and Src dependence distinguishes mesenchymal and amoeboid modes of tumour cell invasion: a link to integrin function

Abstract: Cancer cells can invade three-dimensional matrices by distinct mechanisms, recently defined by their dependence on extracellular proteases, including matrix metalloproteinases. Upon treatment with protease inhibitors, some tumour cells undergo a 'mesenchymal to amoeboid' transition that allows invasion in the absence of pericellular proteolysis and matrix degradation. We show here that in HT1080 cells, this transition is associated with weakened integrin-dependent adhesion, consistently reduced cell surface ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
133
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 52 publications
11
133
0
1
Order By: Relevance
“…One of the defining features of mesenchymal cell motility is the requirement for regulated focal adhesion formation and disassembly Carragher et al, 2006). Mounting evidence suggests that the expression profile of tropomyosin isoforms is an important determinant of focal adhesion structure and function (Gupton et al, 2005;Zheng et al, 2008;Bach et al, 2009;Drappatz et al, 2009;O'Neill, 2009), and we have shown that elevated Tm5NM1 expression induces focal adhesion stabilization (Bach et al, 2009).…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…One of the defining features of mesenchymal cell motility is the requirement for regulated focal adhesion formation and disassembly Carragher et al, 2006). Mounting evidence suggests that the expression profile of tropomyosin isoforms is an important determinant of focal adhesion structure and function (Gupton et al, 2005;Zheng et al, 2008;Bach et al, 2009;Drappatz et al, 2009;O'Neill, 2009), and we have shown that elevated Tm5NM1 expression induces focal adhesion stabilization (Bach et al, 2009).…”
Section: Discussionsupporting
confidence: 49%
“…As Src kinase is a major regulator of focal adhesion stability and mesenchymal motility (Fincham and Frame, 1998;Webb et al, 2004;Carragher et al, 2006), and we have demonstrated that total Src expression is decreased in cells with elevated Tm5NM1 (Bach et al, 2009), we next tested whether Src kinase activity is suppressed. Using antibodies to the activated form of Src kinase, we find significantly decreased activated Src, relative to total Src protein in cells with elevated Tm5NM1 (Figures 3g and h).…”
Section: Tm5nm1 Inhibits Mesenchymal Migrationmentioning
confidence: 99%
See 3 more Smart Citations